Effects of blood flow restriction training on bone metabolism: a systematic review and meta-analysis - Wang, Xiaolin; Wang, Yifei; Yang, Xuezhen; Mohd Nasiruddin, Nasnoor Juzaily Bin; Dong, Delong; Samsudin, Shamsulariffin Bin; Qin, Xin-Min (Frontiers Media, 2023)
Introduction: The efficacy of low-intensity blood flow restriction (LI-BFR) training programs in bone metabolism remains unclear compared to low-intensity (LI) training and high-intensity (HI) training. The aim of this review was to quantitatively identify the effects of LI-BFR training on changes in bone formation markers (i.e., bone-specific alkaline phosphatase, BALP), bone resorption (i.e., C-terminal telopeptide of type I collagen, CTX) and bone mineral density (BMD) compared with conventional resistance training programmes. Additionally, the effectiveness of walking with and without BFR was assessed. Methods: PubMed, Scopus, SPORTDiscus, Web of Science and Google Scholar databases were searched for articles based on eligibility criteria. Review Manager Version 5.4 was used for Meta-analysis. Physiotherapy Evidence Database (PEDro) was applied to assess the methodological quality of studies. Results: 12 articles were included in the meta-analysis, with a total of 378 participants. Meta-results showed that compared with LI training, LI-BFR training induced greater increments in BALP (young adults: MD = 6.70, p < 0.001; old adults: MD = 3.94, p = 0.002), slight increments in BMD (young adults: MD = 0.05, p < 0.00001; old adults: MD = 0.01, p < 0.00001), and greater decrements in CTX (young adults: MD = −0.19, p = 0.15; old adults: MD = −0.07, p = 0.003). Compared with HI training, LI-BFR training produced smaller increments in BALP (young adults: MD = −6.87, p = 0.24; old adults: MD = −0.6, p = 0.58), similar increments in BMD (MD = −0.01, p = 0.76) and similar decrements in CTX (young adults: MD = 0, p = 0.96; old adults: MD = −0.08, p = 0.13). Although there were only two studies on walking training intervention, walking training with BFR had a better effect on bone metabolism than training without BFR. Discussion: In conclusion, LI-BFR training induces greater improvements in bone health than LI training, but is less effective than HI training. Therefore, LI-BFR training may be an effective and efficient way to improve bone health for untrained individuals, older adults, or those undergoing musculoskeletal rehabilitation. Clinical Trial Registration: [ https://www.crd.york.ac.uk/prospero/ ], identifier [CRD42023411837].